Ultrasonic, Molecular and Mechanical Testing Diagnostics in Natural Fibre Reinforced, Polymer-Stabilized Earth Blocks - C. Galán-Marín; C. Rivera-Gómez; F. Bradley (International Journal of Polymer Science)
The aim of this research study was to evaluate the influence of utilising natural polymers as a form of soil stabilization, in order to assess their potential for use in building applications. Mixtures were stabilized with a natural polymer (alginate) and reinforced with wool fibres in order to improve the overall compressive and flexural strength of a series of composite materials. Ultrasonic pulse velocity (UPV) and mechanical strength testing techniques were then used to measure the porous properties of the manufactured natural polymer-soil composites, which were formed into earth blocks. Mechanical tests were carried out for three different clays which showed that the polymer increased the mechanical resistance of the samples to varying degrees, depending on the plasticity index of each soil. Variation in soil grain size distributions and Atterberg limits were assessed and chemical compositions were studied and compared. X-ray diffraction (XRD), X-ray fluorescence spectroscopy (XRF), and energy dispersive X-ray fluorescence (EDXRF) techniques were all used in conjunction with qualitative identification of the aggregates. Ultrasonic wave propagation was found to be a useful technique for assisting in the determination of soil shrinkage characteristics and fibre-soil adherence capacity and UPV results correlated well with the measured mechanical properties.